Hypermucoviscous Klebsiella pneumoniae: A challenge in community acquired infection. (2019) - Sánchez-López, Javier; García-Caballero, Andrea; Navarro-San Francisco, Carolina; Quereda, Carmen; Ruiz-Garbajosa, Patricia; Navas, Enrique; Dronda, Fernando; Morosini, María Isabel; Cantón, Rafael; Diez-Aguilar, María
Highlights: Description of 4 cases outside Asia of invasive infection by hypervirulent K. pneumoniae. These are patients from the community without any type of epidemiological background or previous trips to the endemic area. Unlike other series in our case, these are patients without one of the classic risk factors: no patient is diabetic. Patients present both serotype K1 and K2, not finding a prevalent serotype in our series. Abstract: In 1986, a new syndrome was described in Taiwan secondary to hypervirulent K. pneumoniae (hvKP), and its main feature was the ability to cause severe infection in young and immunocompetent hosts. Their virulence is explained by the efficient acquisition of iron and an increase in capsule production, which confer the characteristic hypermucoviscous phenotype. Most of these cases have been described in Asia and subsequently spread to America and Europe, where their prevalence is much lower. We present four cases of bacteremia and liver abscesses secondary to hypervirulent K. pneumoniae, two of them associated with endophthalmitis . K. pneumoniae isolates recovered from two of the patients belonged to capsular serotype K1 (genes wzx_K1 and magA ), while the other two were K2 (gene wzy_K2 ). Both of the K1 isolates were classified into a ST23, and isolates of serotype K2 belonged to the ST375 and ST881 clones. In Europe, hvKP isolates are less frequently recovered, mostly associated with Asian citizens or travelers, which was not the case in our patients. K1 capsular serotype is a major cause of primary liver abscess and secondary septic embolus, and K2 is associated with secondary liver abscess. Although these hypervirulent variants usually affect immunocompetent patients as in our cases, diabetes mellitus is a major risk factor for the most invasive cases, with concomitant poor prognosis. Identification of hypervirulent K. pneumoniae serotypes K1 and K2 should be considered as part of the microbiological diagnosis of community-acquired liver abscess due to their clinical implications.